In Vivo Screening of Hepatocellular Carcinoma Using AC Susceptibility of Anti-Alpha Fetoprotein-Activated Magnetic Nanoparticles - Chieh, Jen-Jie (Public Library of Science, 2012)
With antibody-mediated magnetic nanoparticles (MNPs) applied in cancer examinations, patients must pay at least twice for MNP reagents in immunomagnetic reduction (IMR) of in vitro screening and magnetic resonance imaging (MRI) of in vivo tests. This is because the high maintenance costs and complex analysis of MRI have limited the possibility of in vivo screening. Therefore, this study proposes novel methods for in vivo screening of tumors by examining the AC susceptibility of bound MNPs using scanning superconducting-quantum-interference-device (SQUID) biosusceptometry (SSB), thereby demonstrating high portability and improved economy. The favorable agreement between in vivo tests using SSB and MRI demonstrated the feasibility of in vivo screening using SSB for hepatocellular carcinoma (HCC) targeted by anti-alpha fetoprotein (AFP)-mediated MNPs. The magnetic labeling was also proved by in vitro tests using SSB and biopsy assays. Therefore, patients receiving bioprobe-mediated MNPs only once can undergo in vivo screening using SSB in the future.